The Influence of Interest, Independence and Learning Resources on Student Learning Achievement in Mathematics Lessons - Diana Syahfitri Nasution; Laili Habibah Pasaribu (Budapest International Research and Critics University, 2021)
This study aims to determine the interest, independence and learning resources of students' learning achievement in mathematics. This research uses descriptive quantitative research. The population of this study were all students of class VII MTS Ar-Ridha Tanjung Mulia. The sample of this study uses a saturated sample, the saturated sample method is a sampling technique when all members of the population are used as the sample. Data collection techniques using a questionnaire or questionnaire with written techniques. The results of data analysis on the influence of interest in multiple regression, namely through the t test, the amount of 0.014 <0.05, it is known that the t count is 3.2k10. The result of independence thus, it is known that the value is 0067> 0.05 t count 1.927 <t table 2.07387. The coefficient of determination to determine the R square of independence (X2).